Lipomatous hypertrophy of the interatrial septum: an unusual intraoperative finding. Issue 1 (January 1991) - Bhattacharjee, M; Neligan, M C; Dervan, P
Abstract : Lipomatous hypertrophy of the interatrial septum was an incidental finding in a man of 45 undergoing coronary artery bypass grafting for unstable angina. He was not overweight and did not have any rhythm disturbances. The diagnosis was made on frozen section.